Formation Of Characters With Good Morals In Social Media - Pradita S, Muhammad Rafi Pradita S (Ulumuddin: Journal of islamics Study, 2025)
Morality is a trait embedded in the soul from which deeds arise easily and simply without requiring thought and consideration. So if that trait gives rise to good and commendable deeds according to reason and sharia, then that trait is called good morality or akhlakul karimah, and if what arises from that trait is bad deeds, then it is called bad morality or akhlakul mazhmumah. The development of technology, especially communication and information technology, is experiencing a golden age, one of which is social media. Social media seems to have become a necessity of human life, every time people access the internet to connect with news developments on social media, such as news from parents, siblings, friends, business partners, or news from a particular group. The purpose of writing this article is to analyze how social media etiquette is in the perspective of Islam. The writing method uses a literature review by referring to several reference sources, both primary and secondary sources from several books, the Qur'an, the Hadith, and journals. Based on the results of the analysis, it is concluded that a Muslim in socializing using social media should always uphold manners in socializing, by respecting fellow creatures of Allah, because every deed done in the world will be accounted for in the hereafter. The benefits of social media are quite numerous to seek the pleasure of Allah SWT, depending on its use, whether it is used for good or bad things.